2005
DOI: 10.1097/01.ana.0000151408.62650.b5
|View full text |Cite
|
Sign up to set email alerts
|

Response Entropy Increases During Painful Stimulation

Abstract: Frontal electromyography (FEMG) may increase during painful stimulation and indicate patient arousal. The Datex-Ohmeda Entropy Module calculates state entropy (SE) of the electroencephalogram (EEG; 0.8-32 Hz) and response entropy (RE) of EEG and FEMG (0.8-47 Hz). We determined whether RE increases above SE (RE--SE), an indication of FEMG, increase during painful stimuli and if this is related to paralysis or level of anesthesia. With the unanesthetized baseline measurement, SE was 89 +/- 2 and RE was 98 +/- 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 10 publications
1
38
2
1
Order By: Relevance
“…It has been reported that the frontal EMG may be of value even in assessing adequacy of anesthesia (22). A recent publication also demonstrates graded responses to pain stimulation associated with different depth of anesthesia (23). Further studies may clarify whether recording of facial or scalp muscle EMG activity is a useful adjunct also for neonatal pain monitoring.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that the frontal EMG may be of value even in assessing adequacy of anesthesia (22). A recent publication also demonstrates graded responses to pain stimulation associated with different depth of anesthesia (23). Further studies may clarify whether recording of facial or scalp muscle EMG activity is a useful adjunct also for neonatal pain monitoring.…”
Section: Discussionmentioning
confidence: 96%
“…In the study regarding RE responsiveness to pain stimulation, RE increased after surgical stimulation and was not dependent on recovery from muscle relaxation [14]. The authors suggest that RE reflects EMG and may be useful to identify inadequate anesthesia and patient arousal during painful stimuli.…”
Section: Discussionmentioning
confidence: 93%
“…RE and SE distinguished very well between conscious and unconscious states and exhibited high sensitivity and specificity in the detection of loss of consciousness. In studies regarding RE responsiveness to pain stimulation [14], RE increased after surgical stimulation and it was shown to predict movement in a patient after stimulation; it was also a better predictor of stimulation than the BIS index combined with hemodynamic responses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wheeler and colleagues demonstrated that Response Entropy, RE-SE difference, Heart Rate and Blood Pressure were significantly increased during painful stimulation. (17) It has been reported that excitability of subcortical structures evoked by noxious stimuli will increase the difference between RE and SE. Takamastu and colleagues also reported that frontal Electromyogram may be of value in assessing adequacy of anaesthesia and also reflects nociception, but it did not correlate with the intensity of the stimulation (18) .…”
Section: Discussionmentioning
confidence: 99%